2018
DOI: 10.1038/s41467-018-06221-1
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin kills malaria parasites by damaging proteins and inhibiting the proteasome

Abstract: Artemisinin and its derivatives (collectively referred to as ARTs) rapidly reduce the parasite burden in Plasmodium falciparum infections, and antimalarial control is highly dependent on ART combination therapies (ACTs). Decreased sensitivity to ARTs is emerging, making it critically important to understand the mechanism of action of ARTs. Here we demonstrate that dihydroartemisinin (DHA), the clinically relevant ART, kills parasites via a two-pronged mechanism, causing protein damage, and compromising parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
230
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(262 citation statements)
references
References 52 publications
23
230
0
Order By: Relevance
“…Several mechanisms have been proposed to explain the role of K13 in ART resistance, including an enhanced cell stress response leading to upregulation of the unfolded protein response, decreased ubiquitination, and increased cell survival (32). Consistent with this model, inhibitors of the proteasome synergize with artemisinin (33, 34). However, other studies have reported the development of delayed clearance or dormancy phenotypes in P. falciparum -infected patients without associated K13 mutations (35, 36).…”
Section: Introductionmentioning
confidence: 59%
“…Several mechanisms have been proposed to explain the role of K13 in ART resistance, including an enhanced cell stress response leading to upregulation of the unfolded protein response, decreased ubiquitination, and increased cell survival (32). Consistent with this model, inhibitors of the proteasome synergize with artemisinin (33, 34). However, other studies have reported the development of delayed clearance or dormancy phenotypes in P. falciparum -infected patients without associated K13 mutations (35, 36).…”
Section: Introductionmentioning
confidence: 59%
“…Responses to oxidative stress and protein damage are shown to mediate emergence of artemisinin resistance in malaria parasites [15, 28, 29, 45, 46]. Interestingly, 775 new PfGCN5 bound sites were acquired under artemisinin stress conditions as indicated by ChIP-sequencing of PfGCN5 (Fig 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitylation is important in mediating the effects of artemisinin. Parasite treatment with artemisinin results in activation of the unfolded protein response and the accumulation of polyubiquitylated substrates, compromising proteasomal function [16,59,60], and the proteostatic dysregulation of parasite phosphatidylinositol 3-kinase (PI3K) [61]. Amino acid substitutions in the K13 Kelch protein are associated with artemisinin resistance, and it has been proposed that K13 is a ubiquitin E3 ligase adaptor for PI3K [61].…”
Section: Discussionmentioning
confidence: 99%
“…K13 and PI3K associate with the parasite ER and potentially involved in quality control of exported and cytoplasmic proteins [62,63]. Interestingly an E1 inhibitor antagonises dihydroartemisinin activity [16] and therefore such compounds would not be useful in combination with artemisinin, but DUB inhibitors such as PR619 may be useful in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation